An integrated robust optimisation approach for energy communities utilising green hydrogen and renewable energy sources under dynamic, policy-driven tariff mechanisms for sustainable development - Sobhan Dorahaki (20545670) (2025)
Green hydrogen offers a transformative opportunity for decentralised clean energy systems by enabling long-term storage and carbon-neutral operations. This study introduces a coordinated energy operation framework designed for Energy Communities (ECs) that integrates community-scale green hydrogen infrastructure and fair internal energy sharing. A novel incentive-driven electricity tariff mechanism is introduced, wherein higher hydrogen export volumes to the upstream grid result in tiered electricity discounts for community members, thereby enhancing energy affordability and encouraging renewable integration. The ECs' shared assets are coordinated by a central EC manager to optimise performance under variable solar conditions. A robust optimisation framework is employed to handle photovoltaic uncertainty, ensuring operational reliability without reliance on probabilistic forecasts. The simulation outcomes indicate that incorporating hydrogen exchange substantially influences the community's overall economic performance. Moreover, the proposed tariff-based approach reduces prosumers' electricity costs by 5.27 % and increases the community's total profit by 3.33 %. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.152756